Direito ao esquecimento no âmbito da propaganda eleitoral - Fiorito, Mauricio (2020)
The use of the right to be forgotten in political advertising is practically nonexistent. We will see the genesis and evolution of popular representation and how the thinking of some philosophers ended up influencing among others, the French Revolution, being the starting point for the inclusion in the core of the constitutions that followed the concern to guarantee fundamental rights to every citizen, such as freedom of expression and thought, the right to information, as well as in opposition, the right to intimacy and privacy. From this conflict of guarantees, under the aegis of the principle of human dignity, comes the right to be forgotten. Its birth, historical references, using the “Lebach case” (Germany 1973) as a milestone, as well as other cases such as Aida Cury, Chacina da Candelaria, Doca Street, Costeja Gonzáles (spanish), Yésica Toscanini (argentinean) and recent decisions regarding the deindexation of content with the internet providers will be analyzed. Would the candidate be totally prevented from using this institute? What if the candidate already has a court decision regarding a past fact? And when a particular media release reaches third parties? Would the applicability of this institute to the digital world be possible? At the end, this work will lead the reader to a reflection in what would be the best option, through the weighting of principles using the proportionality criterion recommended by Alexy. Thus, the present work will use the deductive method and through the study of institutes that guarantee human dignity, will it be seen whether or not it will be applied to political advertising, opposing the right to information to the right of personality.